Oral Iron Treatment for Children with Nutritional Anaemia and Factors that Affect the Results - Shahrukh Yar, Jahanzeb Khan Afridi, Asad Khan, Tanzeel Ur Rahman, Nasar Rashid, Tahir Ahmad (Pakistan Journal of Medical & Health Sciences, 2023)
Background: This study aimed to investigate the efficacy of oral iron therapy in childhood nutritional anaemia and to identify the factors affecting the outcome of 100 patients. Data was collected from the medical records of the patients. The study showed that oral iron therapy was effective in treating childhood nutritional anaemia, with the majority of patients (84%) achieving complete haematological recovery. The factors associated with successful treatment included age, gender, clinical presentation, and duration of iron therapy. The study shows suggest that oral iron therapy is an effective and safe treatment option for childhood nutritional anaemia and that age, gender, clinical presentation, and duration of iron therapy may affect the outcome of treatment. Methodology: This study was conducted department of pediatric hmc hospital Peshawar from jan 2021 to jan 2022 . The study included 100 patients aged between 2 and 12 years with childhood nutritional anaemia. Data was collected from the medical records of the patients, including demographic characteristics, clinical presentation, laboratory results, duration of iron therapy, and outcome of treatment. Descriptive statistics were used to analyze the data and logistic regression analysis was used to identify the factors affecting the outcome of treatment. Results: According to the findings, 84% of the kids who received oral iron therapy for treating childhood nutritional anaemia experienced positive effects. Age (OR=2.5, 95% CI: 1.3-4.7), male gender (OR=2.1, 95% CI: 1.1-4.3), clinical presentation (OR=2.8, 95% CI: 1.3-5.8), and length of iron therapy (OR=1.2, 95% CI: 1.1-1.3) were all linked with successful treatment. Conclusion: The study shows suggest that oral iron therapy is an effective and safe treatment option for childhood nutritional anaemia and that age, gender, clinical presentation, and duration of iron therapy may affect the outcome of treatment. Further studies are needed to confirm these findings and to identify the optimal duration of iron therapy in the treatment of childhood nutritional anaemia. keywords: Childhood nutritional anaemia, Oral iron therapy, Outcome, Factors,